EXPECTATIONS OF COMMUNITY SOCIAL WORKERS FOR THEIR PROFESSIONAL COMPETENCE - Gevorgianienė, Violeta (Socialinė teorija, empirija, politika ir praktika, 2009)
The effects of the community decay are widely discussed in EU. Community work is recognized as the „third“ social work method in order to solve social problems. Additional competencies for social workers are required in community work. The competencies are provided through various trainings. In 2006 Lithuania and 6 other European countries started the Leonardo da Vinci project ,,Community care approach: a strategy for social inclusion", which sought to develop the knowledge and skills of community social workers. Each country has organized trainings within the framework of the project for the community social workers aimed at the development of specific competencies of a social worker in a community. The aim of the given article is to analyze the needs for competencies of community workers from 3 European countries - Hungary, Belgium and Lithuania - which would enable them to work better in/with the communities. The results of the research revealed some differences in the learning needs of the participants of 3 European countries: social workers from Belgium, the country with a longer tradition of community social work, demonstrated the least interest in the development of all competence areas. The results also show an area of concern: Hungarian and Lithuanian social workers fail to consider the research in the field of community needs. Lithuanian trainees demonstrated another significant tendency - alongside with the emphasis on the managerial skills they are trying to specify their new professional status, that is, a new role and identity in their work with the community.
Keywords: Community work; Social worker; Comparative research; Lithuania; Belgium; Hungary